Antibacterial Studies of Penicillin G Loaded Carboxylic Cellulose Acetate Nanoparticles - Ho, Boon-Kui; Chin, Suk Fun; Samuel, Lihan (Biointerface Research in Applied Chemistry, 2022)
Cellulose acetate nanoparticles (CCA NPs) with mean particles sizes of 97 nm were synthesized via the nanoprecipitation process. The antibacterial properties of these CCA NPs were evaluated against Gram (+) and Gram (-) bacteria, respectively. The CCA NPs exhibited good antibacterial activity against Methicillin-resistant Staphylococcus aureus (MRSA) (+), Staphylococcus epidermis (+), Escherichia coli (-), Bacillus cereus (+), and Salmonella typhimurium (-) in range of MIC of 2.5×102 to 5.0×102 µg.mL-1 and MBC of 5.0×102 to 1.0×103 µg.mL-1. Penicillin G (PenG)- loaded CCA NPs demonstrated synergistic antibacterial activities against Gram (+) and Gram (-) bacteria. PenG-loaded CCA NPs also exhibited promising antimicrobial activity against the Methicillinresistant staphylococcus aureus (MRSA) superbug, which is resistant to penicillin G. These promising antibacterial properties suggested that CCA NPs could potentially serve as an alternative potent antimicrobial agent for both Gram (+) and Gram (-) bacteria as well as the superbug MRSA.